Fostering Collaboration for Sustainable Impact: Insights from the ECoGREEN 2024 National Conference on MSMEs Best Practices - Parung, Christabel Annora Paramita (Universitas Pembangunan Jaya, 2024)
This paper analyzes the outcomes of the ECoGREEN 2024 National Conference, which aimed to promote sustainable development through collaboration among stakeholders, including academics, MSMEs, policymakers, and civil society. The conference emphasized sustainability across various domains, such as environmental science, MSMEs, and governmental policy, providing a platform for knowledge exchange and innovative solutions. Key findings highlight the critical role of integrating sustainability reporting, adopting digital and eco-innovative practices, and preserving cultural heritage. The study also underscores the potential of leveraging Industry 4.0 technologies, such as AI and blockchain, to enhance operational efficiency and sustainability performance.This research identifies actionable strategies for MSMEs to overcome challenges such as limited resources, technological gaps, and regulatory barriers. Moreover, it highlights the significance of design thinking and interdisciplinary approaches in fostering sustainable practices. Designers, in particular, can utilize the insights from this conference to integrate zero-waste principles, promote eco-innovation, and preserve cultural heritage in their work. The study demonstrates how collaboration, innovation, and education can address global sustainability challenges while fostering economic, environmental, and cultural resilience.